"A process of controlled serendipity": An exploratory study of historians' and digital historians' experiences of serendipity in digital environments. Issue 1 (24th October 2017) - Martin, Kim; Quan‐Haase, Anabel
ABSTRACT: We investigate historians' experiences with serendipity in both physical and digital environments through an online survey. Through a combination of qualitative and quantitative data analyses, our preliminary findings show that many digital historians select a specific digital environment because of the expectation that it may elicit a serendipitous experience. Historians also create heuristic methods of using digital tools to integrate elements of serendipity into their research practice. Four features of digital environments were identified by participants as supporting serendipity: exploration, highlighted triggers, allowed for keyword searching and connected them to other people.